2009
DOI: 10.1016/j.yjmcc.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cardioprotection by S-nitroso-2-mercaptopropionyl glycine

Abstract: The reversible S-nitrosation and inhibition of mitochondrial complex I is a potential mechanism of cardioprotection, recruited by ischemic preconditioning (IPC), S-nitrosothiols, and nitrite. Previously, to exploit this mechanism, the mitochondrial S-nitrosating agent S-nitroso-2-mercaptopropionyl glycine (SNO-MPG) was developed, and protected perfused hearts and isolated cardiomyocytes against ischemia-reperfusion (IR) injury. In the present study, the murine left anterior descending coronary artery (LAD) occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 80 publications
2
50
0
Order By: Relevance
“…In the mitochondrial respiratory chain, the main source of energy production in cardiac tissue, 11 novel SNO-sites were mapped to the subunits of complexes I-III, including seven modified residues located in six different subunits of complex I. Previous reports have shown that Complex I is S-nitrosated in preconditioning, and that cardioprotection may stem from reduced production of harmful reactive oxygen species (5,7,8,13). The sitespecific information provided here will now allow this hypothesis to be tested.…”
Section: Discussionmentioning
confidence: 86%
“…In the mitochondrial respiratory chain, the main source of energy production in cardiac tissue, 11 novel SNO-sites were mapped to the subunits of complexes I-III, including seven modified residues located in six different subunits of complex I. Previous reports have shown that Complex I is S-nitrosated in preconditioning, and that cardioprotection may stem from reduced production of harmful reactive oxygen species (5,7,8,13). The sitespecific information provided here will now allow this hypothesis to be tested.…”
Section: Discussionmentioning
confidence: 86%
“…However, the latter possibility seems unlikely, since Wort did not affect SNAP's protection in the present study either. The nitrosylating agent S-nitroso-2-mercaptopropionyl glycine given at reperfusion mimics IPC's protection in mouse heart (32), and a PKGindependent action of NO has been proposed to inhibit permeability transition pore formation in mitochondria after IPC [for review see Burwell and Brooks (5)]. In summary, it is not…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in studies of intact hearts, inhibition of complex I (with rotenone) during ischemia preserved mitochondrial cardiolipin and cytochrome c content (246), suggesting a role for ETC leak in cardiolipin oxidation and a possible target to prevent cardiolipin oxidation. Other therapeutic means to regulate ETC leak are being developed, including S-nitrosating compounds, that were discussed previously (306,336), and cationic plastoquinone derivatives (392). The function of GPx-4 to limit specifically mitochondrial phospholipids oxidation has also been explored, as discussed next.…”
Section: Handy and Loscalzomentioning
confidence: 99%